Current Strategies to Enhance Recovery following Radical Cystectomy: Single Centre Initial Experience. (8th March 2012) - Vasdev, Nikhil; Pillai, Praveen L.; Snowdon, Christopher P.; Thorpe, Andrew C.
Abstract : A radical cystectomy (RC) with pelvic lymph node dissection is the gold standard treatment for muscle-invasive bladder carcinoma. The morbidity associated with RC is clearly lower than that in the previous decades; it still continues to remain higher than 30% in the early postoperative period associated with and remains the most effective method for local control. We present current strategies being developed to further enhance recovery in patients undergoing RC and stratifying these into pre, intra, and post operative. We present our current strategies to enhance revcovery in patients undergoing RC which includes a combination of a through preoperative assessment with cardiopulmonary exercise (CPX), preoperative carbohydrate loading drinks, and intraoperative fluid monitoring with the trans-oesophageal Doppler probe (TODP) that may enhance recovery following radical cystectomy. We conclude that using these strategies may not only help in reducing peri/post operative morbidity and the duration of inpatient stay but may also help in enhancing the patient's long-term recovery.